Surgical Treatment of Kimmerle's Anomaly (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Patients with vertebrobasilar insufficiency and pain syndrome, which are frequently encountered in the practice of a neurologist and neurosurgeon, require a comprehensive examination to clarify the etiologic factor in the development of vertebrobasilar insufficiency and conduct differential diagnostics [1,2]. One of the possible causes of this condition is the Kimmerle anomaly - a variant of the structure of the first cervical vertebra (atlas), in which an additional bony arch is formed, extending from the posterolateral part of the lateral mass of the atlas above the groove of the vertebral artery and connecting with its posterior arch, and ossification of a portion of the atlanto-occipital ligament is also possible. The diagnostic complex, in addition to a clinical and neurological examination, includes spondylography, computed tomography and magnetic resonance imaging of the cervical spine, Doppler ultrasound and direct angiography. A dependence of the frequency and severity of neurological syndromes on the severity of the anomaly and the age of the patients has been established. An algorithm for the comprehensive diagnosis and treatment of this pathology has been developed [2]. Along with Arnold-Chiari malformations, platybasia, basilar impression, C1 assimilation, hypoplasia and aplasia of the posterior arch of C1, AC is one of the most common anomalies of the craniovertebral junction [3,4]. AC occurs in 18.8% of cases according to sectional findings, in 17.2% according to the analysis of multispiral computed tomography (MSCT), and in 16.6% according to spondylography [5,6]. The disease occurs equally often in both men and women (15.8% and 14.6%, respectively). According to N. A. Shchikunov (2014), in a study of 305 incidents of congenital AC, a bilateral symmetrical variant was observed in 42% of cases. In this case, a completely symmetrically formed canal was observed in 29% of cases, and an incomplete one in 13%. In 19% of cases, bilateral asymmetric AC was detected; of these, a completely closed canal on the left and an incompletely closed one on the right occurred in 12% of cases, and a completely closed canal on the right and an incomplete one on the left occurred in 7%. Unilateral AC was determined in 39% of cases, of which a left-sided anomaly was noted more often (30%), and a right-sided anomaly less often (9%). In the case of a left-sided canal of the PA, it was incomplete in 16% of cases and complete in 14% [7,8].